The Effectiveness of Incentive Schemes in the Presence of Implicit Effort Costs - Sebastian J. Goerg; Sebastian Kube; Jonas Radbruch (Institute of Labor Economics (IZA), 2017)
Agents' decisions to exert effort depends on the provided incentives as well as the potential costs for doing so. So far most of the attention has been on the incentive side. However, our lab experiments underline that both the incentive and cost side can be used separately to shape work performance. In our experiment, subjects work on a real-effort task. Between treatments, we vary the incentive scheme used for compensating workers. Additionally, by varying the available outside options, we explore the role of implicit costs of effort in determining workers' performance. We observe that incentive contracts and implicit costs interact in a non-trivial manner. Performance reacts significantly to changes in implicit effort costs under low-powered piece-rate and target-based bonus contracts, but not under a high piece rate contract. In addition, comparisons between the incentive schemes depend crucially on the implicit costs.
Keywords: C91; D01; D03; D24; J22; J24; J33; L23; M52; 330; workers' performance; work environments; implicit cost; opportunity costs; incentive schemes